2005
DOI: 10.1261/rna.2050505
|View full text |Cite
|
Sign up to set email alerts
|

In vivo excision of a single targeted nucleotide from an mRNA by a trans excision-splicing ribozyme

Abstract: We have previously reported the development of a group I intron-derived ribozyme that can bind an exogenous RNA substrate and excise from that substrate an internal segment in vitro, which allows for sequence-specific modification of RNA molecules. In this report, the activity of this trans excision-splicing ribozyme in a cellular environment, specifically Escherichia coli, was investigated. The ribozyme was re-engineered to target for excision a single-base insertion in the transcript of a green fluorescent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Expression of eukaryotic pathways in a prokaryote host would appear, at first hand, to be a redundant strategy because of incompatibilities in post-transcriptional mRNA processing. However, eukaryotic expression systems do exist [133], and modification of these or prokaryotic surrogates into 'superhosts' to bypass transcription, translation or biosynthetic barriers could become a reality in the future, for example, by the additional cloning of RNA processing enzymes [134]. Selection of an appropriate host is key to sustainable production on an industrial scale to sustain a future global supply.…”
Section: Molecular Genetic Approaches Towards Sustainable Supplymentioning
confidence: 99%
“…Expression of eukaryotic pathways in a prokaryote host would appear, at first hand, to be a redundant strategy because of incompatibilities in post-transcriptional mRNA processing. However, eukaryotic expression systems do exist [133], and modification of these or prokaryotic surrogates into 'superhosts' to bypass transcription, translation or biosynthetic barriers could become a reality in the future, for example, by the additional cloning of RNA processing enzymes [134]. Selection of an appropriate host is key to sustainable production on an industrial scale to sustain a future global supply.…”
Section: Molecular Genetic Approaches Towards Sustainable Supplymentioning
confidence: 99%
“…GI ribozymes engineered for trans-splicing reactions lack their 5'-exon or 3'-exon and contain designed P1 elements to bind given target RNAs. [8,15] Recently,M üller and co-workersd eveloped an improved system based on the Tetrahymena GI ribozyme,w hich achieved trans-excision splicing in E. coli cells. [9] It has been demonstrated that the ribozymes engineered for trans-splicing reactions target severalR NA sequences not only in Escherichiac oli cells [7,10,11] but also in mammalianc ells.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Several trans-excision-splicing reactions have been reported to date. [8,15] Recently,M üller and co-workersd eveloped an improved system based on the Tetrahymena GI ribozyme,w hich achieved trans-excision splicing in E. coli cells. [16,17] These examples suggested that it might be possible to engineer self-splicinga nd related reactions of GI ribozymes to achieve complex editing of two or more RNA sequences in ac ooperative manner.…”
Section: Introductionmentioning
confidence: 99%
“…Ribozymes have been engineered to repair RNA through removal or addition of small internal fragments as well as single nucleotides based on the group I intron ribozyme [224][225][226] or on the hairpin ribozyme [227]. These systems are true repair systems but until now have been applied only in vitro.…”
Section: Other Strategies Of Ribozyme-mediated Revision Of Rnamentioning
confidence: 99%